The lopsided Christmas cake [large type] - Brunstetter, Wanda E. (Lopsided Christmas cake, 2015)
"New to the community, the Hochstetter twin sisters volunteer to bake a cake for an Amish charity auction, only to learn they must demonstrate the whole process on stage in front of an audience. Their cooking chaos entertains the audience, attracts the attention of more than one bachelor, and opens the door for romance"--